Corporate legal aspects of hospitals in relation to medical malpractice: a review of law no. 17 of 2023 on health - Wicaksono, Emirza Nur (Priviet Social Sciences Journal, 2025)
Decree Law no. 17 of 2023 on Health comes with a new regulation on the responsibility of hospitals for medical negligence. This research aims to examine the juridical impact of the Law's rules on the hospital's liability regime regarding civil, criminal, and administrative liability. This study uses the normative juridical method, which is a statutory and conceptual approach, to examine legal materials through document studies, regulations, literature, and research relevant to the problem of law. The findings reveal that Legislation No. 17 of 2023 concerning Health broadens the legal liability of hospitals as service providers and independent legal entities that are subject to liability. Hospitals need to keep patients safe through the supervision of medical personnel, quality standards, and risk management. These provisions create a multilayer system of accountability that combines the personal responsibility of medical staff with institutional liability, providing greater legal protection for patients and holding healthcare organizations more accountable. The research findings indicate that Legislation No. 17 of 2023 on Health confirms and develops a robust legal basis to reign hospital liability for medical malpractice and foster a structured patient safety culture in healthcare systems.